cDNA library construction and isolation of genes for candidate vaccine antigens from Chrysomya bezziana (the Old World Screwworm fly) - Tony Voucolo; Florentina Supriyanti; Sri Muharsini; Gene Wijffe (Indonesian Center for Animal Research and Development (ICARD), 2000)
The construction and use of cDNA libraries for the isolation of genes encoding candidate antigens for use in a recombinant vaccine against Chrysomya bezziana is described. RNA was isolated and mRNA purified from first and third instar larvae of Chrysomya bezziana and used in the synthesis of two cDNA libraries in the bacteriophage vector λ ZAP express®. These libraries were screened using Digoxigenin-labeled DNA probes obtained from two independent approaches. First, a homolog approach used probes designed from previously characterized peritrophic membrane genes identified from the related myiasis fly, Lucilia cuprina. Secondly, a de novo approach used amino-terminal and internal peptide sequence information derived from purified Chrysomya bezziana peritrophic membrane proteins to generate DNA probes. Three peritrophic membrane genes were identified and characterized. Chrysomya bezziana peritrophin-48 was identified using the homolog approach and, Chrysomya bezziana peritrophin-15 and Chrysomya bezziana peritrophin-42 were identified using the de novo approach. The identification of these genes as encoding candidate antigens against Chrysomya bezziana has allowed the production of recombinant proteins for use in vaccination trials. Key words: cDNA library, peritrophin, peritrophic membrane, Chrysomya bezziana, Lucilia cuprina, vaccine